Effect of Kefir on Soybean Isoflavone Aglycone Content in Soymilk Kefir - Yang, Minke; Yang, Xiaojuan; Chen, Xiaoqu; Wang, Jie; Liao, Zhenlin; Wang, Li; Zhong, Qingping; Fang, Xiang (Frontiers in Nutrition, 2020)
Kefir is a traditional fermented milk originating in the Caucasus area and parts of Eastern Europe. In this study, the kefir culture, which is modified upon the addition of lactic acid bacteria (LAB) cells, specifically for soymilk kefir fermentation with the highest capacity of isoflavone biotransformation, was successfully produced, and the metagenomics composition of soymilk or milk fermented using these kefir cultures was investigated. The metagenome analysis showed that the microbiota of kefir in M-K (milk inoculated with kefir), SM-K (equal volumes of soymilk and milk inoculated with kefir), and S-K (pure milk inoculated with kefir) were related to the addition of soymilk or not. Furthermore, the HPLC chromatogram revealed that Guixia 2 (Guangzhou, China) may be a good source of soymilk kefir fermentation due to its high isoflavone aglycone content (90.23 ± 1.26 μg/g in daidzein, 68.20 ± 0.74 μg/g in genistein). Importantly, the starter culture created by adding 1.5 g probiotics (Biostime®, Guangzhou, China) to Chinese kefir showed a significant increase in the levels of isoflavone aglycones (72.07 ± 0.53 μg/g in isoflavone aglycones). These results provided insight into understanding the suitable soybean cultivar and starter cultures, which exhibit promising results of isoflavone biotransformation and flavor promotion during soymilk kefir fermentation.